Influence of sulfur on selenium absorption in strawberry - Santiago, Franklin Eduardo Melo; Silva, Maria Ligia de Sousa; Ribeiro, Flaviane de Oliveirra; Cipriano, Patriciani Estela; Guilherme, Luiz Roberto Guimarães (Acta Scientiarum. Agronomy, 2018)
Selenium (Se) is an essential mineral element for animals and humans, and attention has been devoted to Se biofortification of agricultural crops. Due to the scarcity of studies aimed at guiding the nutritional Se-enrichment on strawberry and the need to understand the interaction between Se and sulfur (S) in this cultivation, the objective of this study was to evaluate the effect of the application of Se and S levels on the nutrition and production of strawberry. Treatments consisted of five levels of Se (0, 0.3, 0.6, 1.2, and 2.4 mg dm-3 as sodium selenate) and two levels of S (0 and 60 mg dm-3 as gypsum), which were applied in dystroferric Red Latosol soils under greenhouse conditions. The concentration and accumulation of Se are drastically reduced in the shoots and fruits of strawberry with the application of the sulfated fertilization, while absorption of S is maximized with increased levels of Se. Strawberry presents good capacity for nutritional enrichment with Se, which was demonstrated by the accumulation of Se in the fruits, as well as by enhanced fruit yield.